Fueling Climate (In)Action: How organizations engage in hegemonization to avoid transformational action on climate change. Issue 7 (July 2021) - Ferns, George; Amaeshi, Kenneth
This study examines how organizations avoid the urgent need for transformational action on climate change by engaging in a hegemonization process. To show how this unfolds, we draw from Laclau and Mouffe's discourse theory, focusing on the case of BP and its engagement with the climate change debate from 1990 to 2015. Our study takes a longitudinal approach to illustrate how BP defended its core business of producing and selling fossil fuel products by enacting three sequential hegemonization strategies. These included: adopting new signifiers; building 'win-win' relationships; and adapting nodal points. In doing so, we demonstrate how hegemonic construction enables organizations to both incorporate and evade various types of stakeholder critique, which, we argue, reproduces business-as-usual. Our study contributes to organization studies literature on hegemony by highlighting how the construction of hegemony operates accumulatively over an extended period of time. We also contribute more broadly to conversations around political contests and the natural environment by illustrating how the lack of effective climate responses is shaped by temporal dynamics.